Partnerships in early childhood program - Harrison, L; Thomson, C; Longden, T; Valentkine, K; Mullan, K (SPRC Publications see, www.sprc.unsw.edu.au, 2010)
This report summarises the findings from the impact evaluation and the process evaluation. Outcomes data was collected from March 2006 through to November 2007 and interviews for the process evaluation were conducted in August 2006 and October 2007. The PIEC model is based on research linking high quality interventions that focus on developing secure relationships between child care staff and children and improved outcomes for children, particularly high-risk children. Children who are securely attached to staff display more competent interaction with adults and more advanced peer play during child care years. Education and support for parents in fostering secure relationships with children is also conducted. Therefore the evaluation measures focus on changes in the quality of relationships between staff and children, and between parents and children, and follow the social-emotional development of children over the funding period.
SPRC Report 7/10
Keywords: Child Development; Life Events -- Resilience and Adversity; Children -- Outcomes; Children; Families -- Parents and Parenting; Families and relationships; Disadvantage, adversity and resilience; Childhood and child development; Children; Families; Child Development; Life Events; Outcomes; Resilience and Adversity; Parents and Parenting; Adversity and resilience; Families and relationships; Dsiadvantage, adversity and resilience; Childhood and child development